Di fashion: utilizing diffusion models for personalized ‎and high-fidelity generative outfit recommendations - Deshmukh , Krunal; Khade, Arya; Pawar , Vaishnavi; Vyawahare, Sanika; Arti Singh , Ms.; Priyanka ‎Abhale , Mrs. (International Journal of Advanced Mathematical Sciences, 2025)
Artificial intelligence is being used more and more by the fashion industry to ‎boost client interaction and customization. The use of diffusion models, a ‎subclass of generative models, in offering high-fidelity and customized clothing ‎suggestions is examined in this research. Diffusion models gradually convert ‎random noise into comprehensible visual outputs, making them ideal for ‎producing intricate, detailed pictures. They are perfect for producing realistic ‎and eye-catching costume ideas because of their capacity to capture complex ‎materials, patterns, and clothing styles.‎We analyze how these models perform better than conventional techniques ‎like variational autoencoders (VAEs) and generative adversarial networks ‎‎(GANs) in terms of visual quality, variety, and control over the generating ‎process. The paper also emphasizes how diffusion models may be used to ‎create personalized clothing alternatives that represent personal preferences ‎by taking into account user preferences including body type, style, and ‎previous fashion decisions. We also talk about how DiFashion systems may ‎affect many areas of the fashion business, such virtual try-ons and eco-‎friendly clothes. The limitations and future prospects of using diffusion ‎models for fashion recommendation systems are identified in the paper's ‎conclusion, with special attention paid to scalability, user involvement, and ‎computing needs‎.